Dividends, Share Repurchases, and Tax Clienteles: Evidence from the 2003 Reductions in Shareholder Taxes - Blouin, Jennifer L.; Raedy, Jana S.; Shackelford, Douglas A. (The Accounting Review, 2011)
ABSTRACT: This study jointly evaluates firm-level changes in investor composition and shareholder distributions following a 2003 reduction in the dividend and capital gains tax rates for individuals. We find that directors and officers, but not other individual investors, rebalanced their portfolios to maximize after-tax returns in light of the new tax rules. We also find that firms adjusted their distribution policy (specifically, dividends versus share repurchases) in a manner consistent with the altered tax incentives for individual investors. To our knowledge, this is the first study to employ simultaneous equations to estimate both shareholder and managerial responses to the 2003 rate reductions. We find that the generalized method of moments (GMM) estimates are substantially stronger than OLS estimates, consistent with our expectation that investor and manager responses are simultaneously determined. Failure to estimate systems of equations may account for some of the weak and conflicting results from prior studies of the 2003 rate reductions.